Optimal taxation, environment quality, socially responsible firms and investors - Renström, Thomas; Sparato, Luca (Università di Pisa, 2018)
"We characterize the optimal pollution-, capital- and labour-tax structure in a continuous-time growth model in the presence of pollution (resulting from production), both in the first- and second-best, allowing investors to be driven by social responsibility objectives. The social responsibility objective takes the form of warm-glow, as in Andreoni (1990) and Dam (2011), inducing firms to reduce pollution through increased abatement activity. Among the results, the first best pollution tax is still positive under warm-glow, the second-best pollution tax displays the additivity property, and we show the circumstances under which the Chamley-Judd zero capital-income tax result does not hold."